SEVERAL FACTORS AFFECTING AUDITOR’S GOING CONCERN OPINION ON APPAREL AND LUXURY COMPANIES LISTED ON IDX DURING THE COVID-19 PANDEMIC - Amanda, Gabriella; Salim, Susanto (International Journal of Application on Economics and Business, 2025)
The aim of this research is to determine whether there is an influence of company size, leverage and previous year’s going concern audit opinion to the company. The samples used for this research were 57 samples, where the data needed to conduct this research was taken from data from companies listed on the Indonesia Stock Exchange in consumer cyclicals with the Apparel & Luxury Goods sub-sector for 2020-2022. Logistic regression analysis is employed in this study's hypothesis testing to ascertain the impact of company’s size, leverage and previous year’s audit opinion on the going concern opinion. The results of this research are that previous year’s going concern audit opinion has a significant influence on going concern opinion. On the other hand, company size and leverage have no significant influence on going concern opinion.